Combined paraxial-consistent boundary conditions finite element model for simulating wave propagation in elastic half-space media. Issue 70 (March 2015) - Hamdan, N.; Laghrouche, O.; Woodward, P.K.; El-Kacimi, A.
Abstract: In this paper, a finite element model of a soil island is coupled to both a consistent transmitting boundary and a paraxial boundary, which are then used to model the propagation of waves in semi-infinite elastic layered media. The formulation is carried out in the frequency domain while assuming plane strain conditions. It is known that a discrete model of this type, while providing excellent results for a wide range of physical parameters in the context of a half-space problem, may deteriorate rapidly at low frequencies of excitation. This is so because at low frequencies the various waves in the model eventually attain characteristic wavelengths which exceed the distance of the bottom boundary, which then causes that boundary to fail. Also, the paraxial boundaries themselves break down at very low frequencies. In this paper, this difficulty is overcome and the model׳s performance is improved upon dramatically by incorporating an artificial buffer layer sandwiched between the bottom of the soil medium and the underlying elastic half-space. Applications dealing with rigid foundations resting on homogenous or layered half-space media are shown to exhibit significant improvement. Following extensive simulations, clear guidelines are provided on the performance of the coupled model and an interpretation is given on the engineering significance of the findings. Finally, clear recommendations are provided for the practical use of the proposed modelling strategy. Abstract : Highlights: A finite element model capable to simulate wave propagation in semi-infinite media. Ability to deal with homogeneous as well as layered elastic media. Improved performance through the use of a sandwich layer between the soil layer and the underlain half-space. Extensive parametric study to show the improved performance.